2019
DOI: 10.1155/2019/1279658
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Origin of H2S from Volcanic Reservoirs in Niudong Area of the Santanghu Basin, NW China

Abstract: A series of samples including natural gas, formation water, and rocks were collected from volcanic rock reservoirs in the Niudong area of the Santanghu Oilfields and analyzed for their mineral and/or chemical compositions and sulfur and carbon isotopes in order to investigate the occurrence and origin of hydrogen sulfide (H2S). H2S was mostly dissolved in the formation water along with petroleum production in the study area. The δ34S values of on-well H2S samples varied in a range of 9.2‰ to 20.5‰, probably in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In fact, H₂Sgenerationmay even be in direct competition to hydrocarbon generation (a heterotrophic relationship) as methanogenesis (the generation of methane CH 4 , the foundational aliphatic hydrocarbon) from peat bog sources may be delayed due to the effect of these sulphatereducing microorganisms (SRMs) [36]. A sample study from the Santanghu Basin found that the 34 S isotopologue contributed up to a fifth of the sulphur in the areal H₂S and concluded that TSR and/or the thermal decomposition of sulphur (TDS) was/were the key generation mechanism(s) [37] and listed a TSR formation equation as thus [38]:…”
Section: Generationmentioning
confidence: 99%
“…In fact, H₂Sgenerationmay even be in direct competition to hydrocarbon generation (a heterotrophic relationship) as methanogenesis (the generation of methane CH 4 , the foundational aliphatic hydrocarbon) from peat bog sources may be delayed due to the effect of these sulphatereducing microorganisms (SRMs) [36]. A sample study from the Santanghu Basin found that the 34 S isotopologue contributed up to a fifth of the sulphur in the areal H₂S and concluded that TSR and/or the thermal decomposition of sulphur (TDS) was/were the key generation mechanism(s) [37] and listed a TSR formation equation as thus [38]:…”
Section: Generationmentioning
confidence: 99%
“…However, the constant action of acid gas under a high‐temperature condition could lead to the wearing and tearing of the casings and the propagation of cracks in the cement sheath 4 . In addition, high H 2 S leakage during gas production also leads to adverse environmental, health, and safety issues that limit the field development processes 5–10 . In this situation, experts could either abandon the well or execute a special well workover operation 11…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition, high H 2 S leakage during gas production also leads to adverse environmental, health, and safety issues that limit the field development processes. [5][6][7][8][9][10] In this situation, experts could either abandon the well or execute a special well workover operation. 11 Workover operations in DCRs are usually challenging coupled with the potential emission of toxic H 2 S gases that endanger the successful completion of the operation.…”
mentioning
confidence: 99%
“…Since then, the Tuha Oilfield has adopted various measures to increase the production of TVOR. However, due to the tight pores of the reservoir itself, the difficulty of oil flow, and the lack of natural energy, the single-well production of TVORs has been very low. In recent years, with the continuous change of development ideas, the combined development technology of horizontal wells, volume fracturing, and water injection huff and puff (WIHP) has been gradually conducted in the TVOR of the Tuha Oilfield . This combined technology has to some extent alleviated the problem of low and fast declining production from single wells in the TVOR, and some old wells have even experienced a sudden increase in production, which has provided important insights for achieving high and stable production from the TVOR in the Tuha Oilfield.…”
Section: Introductionmentioning
confidence: 99%